2003
DOI: 10.1093/bja/aeg266
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 1% and 2% lidocaine epidural anaesthesia combined with sevoflurane general anaesthesia utilizing a constant bispectral index

Abstract: To maintain BIS of 40-50 during combined epidural/general anaesthesia for lower abdominal surgery, sevoflurane concentrations were lower and less variable with lidocaine 2% than with 1%. In addition, the larger concentration of lidocaine suppressed the stress hormone responses better.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
5

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 11 publications
0
12
0
5
Order By: Relevance
“…Lidocaine significantly reduced morphine consumption (median [25-75% interquartile range]; 8.5 mg[4567891011121314151617] vs. 25 mg[1920212223242526272829303132]; P < 0.0001), post-operative pain scores ( P < 0.05) and hyperalgesia extent on post-operative day 1-day 2-day 4 (mean ± standard deviation (SD); 1.5 ± 0.9 vs. 4.3 ± 1.2 cm ( P < 0.001), 0.6 ± 0.5 vs. 2.8 ± 1.2 cm ( P < 0.001) and 0.13 ± 0.3 vs. 1.2 ± 1 cm ( P < 0.001), respectively). Time to first flatus (mean ± SD; 29 ± 7 h vs. 48 ± 15 h; P < 0.001) and 6MWT at day 4 (189 ± 50 m vs. 151 ± 53 m; P < 0.001) were significantly enhanced in patients with i.v.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lidocaine significantly reduced morphine consumption (median [25-75% interquartile range]; 8.5 mg[4567891011121314151617] vs. 25 mg[1920212223242526272829303132]; P < 0.0001), post-operative pain scores ( P < 0.05) and hyperalgesia extent on post-operative day 1-day 2-day 4 (mean ± standard deviation (SD); 1.5 ± 0.9 vs. 4.3 ± 1.2 cm ( P < 0.001), 0.6 ± 0.5 vs. 2.8 ± 1.2 cm ( P < 0.001) and 0.13 ± 0.3 vs. 1.2 ± 1 cm ( P < 0.001), respectively). Time to first flatus (mean ± SD; 29 ± 7 h vs. 48 ± 15 h; P < 0.001) and 6MWT at day 4 (189 ± 50 m vs. 151 ± 53 m; P < 0.001) were significantly enhanced in patients with i.v.…”
Section: Resultsmentioning
confidence: 99%
“…morphine given as titration in the PACU were 0 and 6 mg [0-9] in the Lidocaine and Reference groups respectively ( P < 0.001). Median cumulative morphine consumption at the end of post-operative day 2 was 8.5 mg [4-17] in the Lidocaine group and 25 mg[1920212223242526272829303132] in the Reference group ( P < 0.0001) [Figure 1]. Pain intensity was significantly reduced in the Lidocaine group both at rest and during coughing ( P < 0.0001) throughout the 48-h study [Figure 2].…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that epidural administration of 15 mL of 2% lidocaine reduced by 34% the sevoflurane required for adequate depth of anesthesia. 6 Shono et al 13 showed that 2% lidocaine rather than 1% lidocaine administration has resulted in both better control of the surgical stress response and significantly more sevoflurane-sparing effect when sevoflurane concentration was titrated according to BIS values. It is suggested that the intensity and extent of epidural block also has influence on inhalational anesthetic requirement.…”
Section: Discussionmentioning
confidence: 99%
“…Wird Lidocain für periphere Nervenblockaden oder zur Periduralanästhesie verwendet, werden in der Regel Plasmakonzentrationen von 3-5 µg/ml erreicht [17,34]. Toxizitätszeichen können ab einem Plasmaspiegel von 5 µg/ml auftreten, werden jedoch eher beobachtet, wenn Plasmaspiegel von mehr als 10 µg/ml erreicht werden.…”
Section: Risikenunclassified